Psychobiotics: the Influence of Gut Microbiota on the Gut-Brain Axis in Neurological Disorders - Oroojzadeh, Parvin; Bostanabad, Saber Yari; Lotfi, Hajie (Journal of molecular neuroscience, 2022)
Nervous system disorders are one of the common problems that affect many people around the world every year. Regarding the beneficial effects of the probiotics on the gut and the gut-brain axis, their application along with current medications has been the subject of intense interest. Psychobiotics are a probiotic strain capable to affect the gut-brain axis. The effective role of Psychobiotics in several neurological disorders is documented. Consumption of the Psychobiotics containing nutrients has positive effects on the improvement of microbiota as well as alleviation of some symptoms of central nervous system (CNS) disorders. In the present study, the effects of probiotic strains on some CNS disorders in terms of controlling the disease symptoms were reviewed. Finding suggests that Psychobiotics can efficiently alleviate the symptoms of several CNS disorders such as autism spectrum disorders, Parkinson’s disease, multiple sclerosis, insomnia, depression, diabetic neuropathy, and anorexia nervosa. It can be concluded that functional foods containing psychotropic strains can help to improve mental health. Graphical Abstract